Impact of Age on The Gender Pay Gap in The Czech Republic - Kamila Veselá (Communications of International Proceedings, 2021)
In the 21st century, gender inequality continues to be an issue in practically the majority of countries around the world. Unfortunately, the Czech Republic does not fare well in international comparison, particularly with regard to the gender pay gap. Some aspects of the gender approach, such as equal access to education, are of a high standard in the Czech Republic, while elsewhere the Czech Republic is below the European average. This is particularly true of the aforementioned pay gap, or the proportion of women in decision-making in public life. The aim of this article is to assess the state and trend of the gender pay gap in the Czech Republic with an emphasis on the role played by age. The article thus answers the question of what role age plays in the gender pay gap. For this, the article draws particularly on an analysis of secondary data in the form of a timeline analysis, a regression analysis, a trend analysis and other suitable methods. The research confirmed that despite the fact that absolute differences in remuneration between men and women increase according to age, an analysis of the trend in the ratio between the wages of men and women shows that it is decreasing in the long term and that wages are starting to align. The only exception is the over-60 age category, where the pay gap is actually increasing.
Keywords: Age; Gender; Inequality; Wage